Space-time clustering of childhood leukemia in Colombia: a nationwide study - Rodriguez-Villamizar, Laura Andrea (BMC Cancer, 2020)
BACKGROUND: Leukemia is the most common cancer in childhood. The estimated incidence rate of childhood leukemia in Colombia is one of the highest in America and little is known about its spatial distribution. PURPOSE: To explore the presence of space-time clustering of childhood leukemia in Colombia. METHODS: We included children less than 15 years of age with confirmed diagnosis of acute leukemia reported to the national surveillance system for cancer between 2009 and 2017. Kulldorff’s spatio-temporal scan statistics were used with municipality and year of diagnosis as units for spatial and temporal analysis. RESULTS: There were 3846 cases of childhood leukemia between 2009 and 2017 with a specific mean incidence rate of 33 cases per million person-years in children aged 0–14 years. We identified five spatial clusters of childhood leukemia in different regions of the country and specific time clustering during the study period. CONCLUSION: Childhood leukemia seems to cluster in space and time in some regions of Colombia suggesting a common etiologic factor or conditions to be studied.